Гібридні алгоритми самоорганізації моделей для прогнозування складних процесів - Степашко, В.С.; Булгакова, О.С.; Зосімов, В.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
A new kind of GMDH algorithm of hybrid type is proposed combining both multilayered and combinatorial schemes for model self-organization and includes the following main novelties: using initial arguments in each layer to avoid loosing the relevant ones; optimization of every partial model structure by combinatorial algorithm to avoid overfitting.